Spanish Negative Concord Items: Experimental Evidence for Their Status as Strict Negative Polarity Items - Vergara, Daniel (International Journal of Language and Literary Studies, 2024)
This study investigates the semantic status of Spanish Negative Concord Items (NCIs) through their comparison with English Negative Quantifiers (NQs) and Polarity Items (PIs) in acceptability judgment tasks conducted among native speakers of Spanish and English. NCIs exhibit a dual behavior depending on their syntactic context, which has resulted in various analyses that categorize them as NQs, PIs, or non-negative indefinites. The findings from this investigation provide experimental confirmation that Spanish NCIs behave like strict Negative Polarity Items (NPIs) or indefinites that are exclusively licensed by a syntactically local anti-veridical operator (i.e., negation). This experimental approach sheds light on the longstanding controversy surrounding the semantic characterization of Spanish NCIs and contributes to our understanding of their behavior across a wide array of linguistic contexts.